Synthetic carbohydrate-based cell wall components from Staphylococcus aureus. (December 2020) - Berni, Francesca; Enotarpi, Jacopo; Voskuilen, Thijs; Li, Sizhe; van der Marel, Gijs A.; Codée, Jeroen D.C.
Graphical abstract: Highlights: A review on the immunogenic glycol-based structures from S. aureus is reported. Immunological evaluation of PNAG and dPNAG biofilm from both native sources as well-defined synthetic fragments. The synthetic strategy towards trisaccharide units of three main capsular polysaccharides (CP5, CP8 and strain M). An overview of several teichoic acids fragments and their application in biological studies. Abstract : Glycopolymers are found surrounding the outer layer of many bacterial species. The first uses as immunogenic component in vaccines are reported since the beginning of the XX century, but it is only in the last decades that glycoconjugate based vaccines have been effectively applied for controlling and preventing several infectious diseases, such as H. influenzae type b (Hib), N. meningitidis, S. pneumoniae or group B Streptococcus . Methicillin resistant S. aureus (MRSA) strains has been appointed by the WHO as one of those pathogens, for which new treatments are urgently needed. Herein we present an overview of the carbohydrate-based cell wall polymers associated with different S. aureus strains and the related affords to deliver well-defined fragments through synthetic chemistry.